Campaign Prop Handling by Bandung City Bawaslu in Realizing Environmental Cleanliness - Suhermanudin, Suhermanudin; Aqil, Nia Pusparini; Wulandari, Rafih Sri; Rahmayanti, Rahmayanti; Permana, Muhammad Fadhilah; Cantika Deni, Destrina Nurfajri; Maulidini, Resti; Putrie, Nindya Nuryulinda; Ramadhan, Gelar Fajar (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
The policies passed and stipulated by the government in the election to pay attention to the optimization of Bawaslu's policies in Law No.7 of 2017 concerning general elections as election organizers and the optimization of Bawaslu's policies regarding the control of campaign props in General Election Commission Regulation No. 20 of 2023 on the amendment of General Election Commission Regulation No. 15 of 2023 this regulation shows the government's attention so that the elections are held properly, in accordance with applicable regulations. The conceptual control model will make it easier for policy implementers to be on target, by realizing the control of campaign props in accordance with the targets, as well as zoning areas that have been set in Bandung City. The research used is based on the skinative method and descriptive analysis, through the Hasibuan theory including direct control, indirect control, and exception control related to the handling of campaign props by the Bandung City Bawaslu